Molecular characterization, Antifungal susceptibility to fluconazole and Analysis of risk factors in patients with Candida auris blood stream infection from Tertiary Care Hospital in North India - Bhartiya, Chitra; Marak, Rungmei SS; Singh, RS; Rawat, Pratima; Sahu, Chinmoy; Dixit, Ajai Kumar; Tripathi, Shikha (International Journal of Human and Health Sciences (IJHHS), 2023)
Aim and objectives: To analyse the risk factors, molecular characterization and detection of drug resistance to fluconazole in Candida auris candidemia. Material and methods: BACTEC blood culture positive for candida on Gram stain from January 2017-December 2020 were inoculated on SDA plate and incubated for at 37ºC for the isolation of yeast colonies. The isolates were subjected to phenotypic identification, PCR and MALDI-TOF MS and antifungal susceptibility testing to fluconazole by Etest method. Demographic details of the patients were recorded and significant associated risk factors were analysed. Results: A total of 59689 blood cultures were received during the study period from admitted patients. There was 623 episodes of candidemia during the study and 111 episodes was due to C. auris. Incidence of candidemia due to C. auris was 17%. The associated risk factors were diabetes mellitus (p <0.024), underlying respiratory illness (p <0.013), mechanical ventilation (p <0.009), dialysis (p <0.034), prolonged ICU stay (p <0.009), hypertension (p <0.035) and others included use of broad-spectrum antibiotics (94.5%) and steroids (23.4%). Only 9% (n=10) isolates were sensitive to fluconazole; 85.6% (n=95) were resistant and 5.4% (n=6) were sensitive dosedependent. Study showed mortality in 36%. Conclusions: Emergence of Candida auris infection has caused a significant threat in patients admitted to the ICUs and is known to cause outbreaks in healthcare facilities. Strict precautions like barrier nursing, hand hygiene and proper infection control practices must be followed as well as use of appropriate antifungal therapy to prevent and control the spread of C. auris. International Journal of Human and Health Sciences Supplementary Issue 02: 2023 Page: S34-S48